Values of Local Wisdom in Traditional Games Penyu Mataluh in Serangan: Study Ethnopedagogy - Rasna, I Wayan; Pande Tresnayani, Ni Putu (Universitas Pendidikan Ganesha, 2021)
This study aims to examine the form and value of local wisdom contained in the traditional game of the penyu mataluh in Serangan from an ethnopedagogy point of view. The research data are in the form of descriptions of body movements in the steps of the game and song lyrics that show the value of local wisdom. Sources of data in this study are children who play the traditional game of the penyu mataluh and the community. The data collection method is the method of listening, taking notes, observing, and interviewing. The data analysis technique used is descriptive analysis including data reduction, data presentation, and drawing conclusions. The results showed that the penyu mataluh game has a form of local wisdom in the form of words, namely, poetry that is sung when playing and actions in the form of body movements that are reflected in the steps of the game. This game can be preserved by making game applications that can be downloaded on mobile phones similar to the original game, teaching the game in schools and cultural studios, and more research on local wisdom on traditional games.